A study on hearing screening using oto-acoustic emissions in newborns delivered by normal vaginal delivery and lower segment caesarean section - Appathurai, Swathi; Jaiswal, Ashwin Ashok; Saha, Subodh Kumar; Dora, Arun Kumar; Mene, Prachi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Hearing is one of the most complex systems of the human body and is a skill involved in the human social evolution. It has been estimated that around 900 million people by the end of 2050, will probably suffer from hearing loss. Our study aims to find out the correlation between the mode of delivery and the effect it has on newborn hearing screening. Methods: The Prospective study on 136 Newborn babies who were delivered in JLN Hospital & Research Centre, Bhilai, Chhattisgarh during October 2020 to August 2021. After obtaining detailed history all newborns underwent TEOAE screening and the data were then compared with the available literature. Results: We observed normal vaginal delivery newborns have passed the test by 97.91% and 89.58% when compared to LSCS delivered infants 97.15% and 86.36% in screening and diagnostic frequency respectively. COVID-19 infection was seen in 2.94% of pregnant mothers in the 3rd trimester. There were no babies who required BERA in our study Conclusions: Normal vaginally delivered newborns have higher pass rate in TEOAE test when compared with LSCS delivered babies. Covid-19 infection in antenatal mother can influence the outcome in 1st TEOAE tests. The pass rate in TEOAE hearing test in the screening frequency is found to be greater when compared with diagnostic frequencies. In a developing country like India, Universal hearing screening programs needs to be reached out to the most remote parts of the country, in order to identify at risk infants for hearing loss.